Pengalaman Pasien Vertigo di Wilayah Kerja Puskesmas Lingkar Timur - Muhammad Amin; Yurike Ade Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the analysis of vertigo patient experience in the work area of ​​the East Lingkar Health Center. The study design was qualitative with a phenomenological model on five informants taken with the snowball sampling technique. The results of interviews that have been prepared through the transcript process and obtained five themes, namely: 1) aspects of knowledge, four informants can explain vertigo based on experience when experiencing dizziness; 2) aspects of clinical manifestations, all informants complained of headaches, nausea, but no vomiting, only vomiting; 3) etiological issues, all informants acknowledge that they experience stress and have sleep problems or sleep disorders; 4) historical aspects, four informants had experienced vertigo before; 5) handling issues, all informants were only given medication by doctors and suggestions for adequate rest and not too much thought. In conclusion, the experience of vertigo patients, form knowledge, there are differences in vertigo with ordinary headaches where the level of vertigo pain is much higher and is accompanied by a sense of object/spinning environment. Keywords: Experience, Vertigo Patients